New Solvent for Polyamide 66 and Its Use for Preparing a Single-Polymer Composite-Coated Fabric - Mostafa Jabbari; Mikael Skrifvars; Dan Åkesson; Mohammad J. Taherzadeh (International Journal of Polymer Science)
Polyamides (PAs) are one of the most important engineering polymers; however, the difficulty in dissolving them hinders their applications. Formic acid (FA) is the most common solvent for PAs, but it has industrial limitations. In this contribution, we proposed a new solvent system for PAs by replacing a portion of the FA with urea and calcium chloride (FAUCa). Urea imparts the hydrogen bonding and calcium ion from the calcium chloride, as a Lewis acid was added to the system to compensate for the pH decrease due to the addition of urea. The results showed that the proposed solvent (FAUCa) could readily dissolve PAs, resulting in a less decrease in the mechanical properties during the dissolution. The composite prepared using the FAUCa has almost the same properties as the one prepared using the FA solution. The solution was applied on a polyamide 66 fabric to make an all-polyamide composite-coated fabric, which then was characterized. The FAUCa solution had a higher viscosity than the one prepared using the neat FA solvent, which can be an advantage in the applications which need higher viscosity like preparing the all-polyamide composite-coated fabric. A more viscous solution makes a denser coating which will increase the water /gas tightness. In conclusion, using the FAUCa solvent has two merits: (1) replacement of 40% of the FA with less harmful and environmentally friendly chemicals and (2) enabling for the preparation of more viscous solutions, which makes a denser coating.